2005
DOI: 10.1002/0471142727.mb2606s72
|View full text |Cite
|
Sign up to set email alerts
|

RNAi in Transgenic Plants

Abstract: RNA silencing in plants is a rapid and facile approach for assignment of gene function and virus resistance. It allows selective RNA degradation through a mechanism that is given specificity by short interfering RNAs. The RNA silencer sequences are normally delivered as transgenes or a part of virus-vectors. This unit provides Basic Protocols for transgene and virus induced silencing. It also includes a Basic Protocol for protein overexpression using viral proteins that suppress silencing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…RNAi silencing is a useful technique to characterize gene function; however, this approach may not generate clear phenotypes due to the threshold level needed for effective silencing (Lindbo et al ). RNAi target genes generally have reduced expression rather than being fully silenced (Yin et al ), thus sufficient transcript may remain to maintain wild type function. This partial reduction in gene expression was seen in HvMS1RNAi silencing (Fernández Gómez and Wilson 2014), where pollen development was affected by the silencing and showed a partial sterile phenotype.…”
Section: New Tools For Translation Analysismentioning
confidence: 99%
“…RNAi silencing is a useful technique to characterize gene function; however, this approach may not generate clear phenotypes due to the threshold level needed for effective silencing (Lindbo et al ). RNAi target genes generally have reduced expression rather than being fully silenced (Yin et al ), thus sufficient transcript may remain to maintain wild type function. This partial reduction in gene expression was seen in HvMS1RNAi silencing (Fernández Gómez and Wilson 2014), where pollen development was affected by the silencing and showed a partial sterile phenotype.…”
Section: New Tools For Translation Analysismentioning
confidence: 99%
“…This complete sterility may be due to the increased transgene copy number in the T1 generation, increasing the silencing capacity beyond the required threshold level (Lindbo et al, 1993). This is a common occurrence, with RNAi lines frequently showing reductions in expression 'knocked down', rather than complete silencing 'knockouts' of the target gene (Yin et al, 2005). For example, (Moritoh et al, 2005) reported that in rice RNAi silencing of the OsGEN-like gene, a member of the RAD2/XPG nuclease family involved in microspore development, caused male sterility, but plants showed variable fertility depending on the expression level of the native gene.…”
Section: The Hvms1 Gene Plays a Critical Role In Pollen Developmentmentioning
confidence: 99%
“…Waterhouse's group showed that 98 to 853 bp hairpin RNA constructs can cause efficient silencing in different plant species, and inclusion of an intron as a spacer between the inverted repeats can improve the efficiency to 90%-100% of transgenic lines showing silencing [142] . Several vector systems have been developed to make constructs containing inverted repeats for expressing dsRNA in transgenic plants, such as ChromDB, Hellsgate, pHANNIBAL, pX7-RNAi and alcR-RNAi, and these have been reviewed by Yin et al [143]…”
Section: Gene Silencing: Discovery and Applications Of Antisense Genementioning
confidence: 99%